The Transformation of Elopement: From Social Stigma to Practical Solution: A Comparative Study of Elopement Practices Among Indonesian Youth - Harun, Nurlaila; Ahyani, Hisam; Kuklys, Indrius; Siripipatthanakul, Supaprawat (Kawanua International Journal of Multicultural Studies, 2024)
This research examines the transformation of meanings and practices of elopement among Indonesian youth, which has shifted from being a stigma to becoming a pragmatic solution in facing contemporary socio-economic challenges. Through comparative analysis across 18 different regions in Indonesia, this research reveals how elopement has evolved from being traditionally stigmatized to an increasingly accepted alternative for young couples. Utilizing a mixed-method approach combining document analysis, semi-structured interviews with 10 young couples, and comparative regional studies, this research identifies three primary economic drivers: rising costs of traditional weddings (ranging from 20 to 500 million rupiah), pressure to own a house before marriage, and changing financial priorities among youth. The findings indicate that urban youth are actively reinterpreting traditional practices to meet modern demands while maintaining cultural legitimacy. This research documents various regional terms and practices, from merariq in Lombok, which is considered honorable, to silariang in Bugis/Makassar society, which is still viewed as a disgrace. This transformation reflects broader changes in Indonesian society, where pragmatic considerations increasingly take precedence over traditional cultural rules, although elements of traditional practices are often preserved through modified forms that accommodate both cultural heritage and modern realities.